Survey and Rapid Detection of Bordetella pertussis in Clinical Samples Targeting the BP485 in China - Liu, Wei; Xu, Yinghua; Dong, Derong; Li, Huan; Zhao, Xiangna; Li, Lili; Zhang, Ying; Wei, Xiao; Wang, Xuesong; Huang, Simo; Zeng, Ming; Huang, Liuyu; et al. (Frontiers in Public Health, 2015)
Bordetella pertussis is an important human respiratory pathogen. Here, we describe a loop-mediated isothermal amplification (LAMP) method for the rapid detection of B. pertussis in clinical samples based on a visual test. The LAMP assay detected the BP485 target sequence within 60 min with a detection limit of 1.3 pg/μl, a 10-fold increase in sensitivity compared with conventional PCR. All 31 non-pertussis respiratory pathogens tested were negative for LAMP detection, indicating the high specificity of the primers for B. pertussis. To evaluate the application of the LAMP assay to clinical diagnosis, of 105 sputum and nasopharyngeal samples collected from the patients with suspected respiratory infections in China, a total of 12 B. pertussis isolates were identified from 33 positive samples detected by LAMP-based surveillance targeting BP485. Strikingly, a 4.5 months old baby and her mother were found to be infected with B. pertussis at the same time. All isolates belonged to different B. pertussis multilocus sequence typing groups with different alleles of the virulence-related genes including four alleles of ptxA, six of prn, four of tcfA, two of fim2, and three of fim3. The diversity of B. pertussis carrying toxin genes in clinical strains indicates a rapid and continuing evolution of B. pertussis. This combined with its high prevalence will make it difficult to control. In conclusion, we have developed a visual detection LAMP assay, which could be a useful tool for rapid B. pertussis detection, especially in situations where resources are poor and in point-of-care tests.